“Rational, Emotional, Affective Learning” and the Use of Innovative Methods in Foreign Language Teaching - Frascà, Paolo (Nouvelle Revue Synergies Canada, 2016)
Foreign language didactics is a field which, notwithstanding the many centuries of application and development, is still very methodologically problematic. Statistics clearly show that, in certain countries, the educational system provides foreign language instruction that is not apt and does not deliver effective linguistic competence; a few methods, however, have been developed to contravene this problem. In the specific case of Italy, a country which is renowned for its general monolingualism, Associazione Culturale Linguistica Educational (ACLE) has developed an innovative language teaching method (Rational, Emotional, Affective Learning) to attempt to fill the lacunae of the Italian school system, especially in regards to the teaching of English as a foreign language. This paper seeks to briefly outline the REAL method and its applications, describe its affinity to didactic and cognitive theories, and speculate on its potential effectiveness.